Standardization of the APC Resistance Test. Effects of Normalization of Results by Means of Pooled Normal Plasma - Tripodi, Armando; Chantarangkul, Veena; Negri, Barbara; Mannucci, Pier Mannuccio (Thrombosis and Haemostasis, 1998)
Results for APC resistance tests are expressed as the ratio of the clotting time with and without APC (APC ratio). Normalization by dividing the patient’s APC ratio by that of the pooled normal plasma (PNP) (n-APC ratio) was proposed to minimize between-lot reagent variability. To evaluate the merits of different expressions of the results, sets of 80 coded frozen plasmas from carriers (n = 30), non-carriers (n = 30) of the FV:Q506 mutation and 10 copies each of two control plasmas were sent to 7 expert laboratories which were asked to assess APC resistance by their methods. Results were expressed as APC ratio and nAPC ratio by the local PNP and 2 common PNP (A and B). These contained plasmas from the same (n = 20) non-carriers. In PNP A, plasma from one non-carrier was replaced with that from one heterozygous carrier. The merits of different expression of results were judged by (i) within-laboratory reproducibility; (ii) discrimination of carriers from non-carriers; (iii) between-method comparability of results. The influence of FV:Q506 plasma in the preparation of PNP was also assessed. Reproducibility, generally good even with results expressed as APC ratio (median CV 4.6% and 3.0% for normal and abnormal control), was not changed by normalization. Discrimination did not change whatever the method of result expression. Between-method comparability of results was scarcely affected by normalization with the local PNP, whereas it was considerably improved after normalization with the common PNP, but only for the non-carriers. APC ratios for PNP A by all methods were significantly lower than those for PNP B. Thus, the presence of mutant FV in a proportion as low as 2.5% may reduce the APC ratio of the PNP.